PENGARUH STUDENT TEAM ACHIEVEMENT DIVISION TERHADAP HASIL BELAJAR SISWA TEMATIK KELAS V SEKOLAH DASAR - yarso, Rohana; Marli, Suhardi; Sugiyono, Sugiyono (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to investigate the effect of Student Team Achievement Division on thematic learning achievement of 5th grade students of Public Elementary School 36 Pontianak Selatan. This study uses an experimental method with pre-experimental design with experimental design of one-group pretest-posttest design. The population of this research was all of 5th totaling 54 students. The sampling technique uses non probability sampling with purposive sampling type and the sample are 5thB grade students totaling 28 students. Data collection techniques use measurement techniques.Data collection tools in the form of multiple choice test totaling 50 question. Based on data analysis result, average of pretest 55,57and posttest 69,21. Result of t-test obtained tcount = 8,27 and ttable (Î± = 0,05; dk =28-1= 27) = 2,05.Means there is a significant difference, because tcount > ttable, its mean H0 rejected and Ha accepted. The effect size result was 0,77 with medium criteria. The conclusion, that Student Team Achievement Division gives effect with medium criteria to thematic learning achievement of 5th grade students of Pontianak Selatan 36 Public Elementary School. Â Keyword : The Effect, Student Team Achievement Division, Learning Achievement, Thematic Learning